THE TECHNOLOGY AS A TOOL FOR ACCESS TO JUSTICE: ONLINE CONCILIATION AND ITS APPLICABILITY IN THE LEGAL FIELD (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
Conciliation by videoconference has intensified, not only because of its role as an alternative means of conflict resolution, in the creation of a solution for the parties themselves, but also because of its need, due to the insertion of technological means in the legal field. Thus, the new technologies implemented support a faster view of production and allow easier access to the means of conflict resolution, which fosters the notion that the adoption of such resources can further consolidate the principle of access to justice, constitutionally provided for. In light of this scenario, the objective of this work is to analyze the occurrence of virtual conciliations in our current context and its consequences in the legal field, given the possibility of procedural speed, as well as in society, due to access to justice by digital means . Thus, based on the literature review methodology, the aim is to verify the benefits and barriers that online conciliation hearings face, identifying whether they in fact intensify constitutional principles and facilitate communicability, or whether access to justice is impracticable.